2017
DOI: 10.3390/nu9080892
|View full text |Cite
|
Sign up to set email alerts
|

Familial Resemblance in Dietary Intakes of Children, Adolescents, and Parents: Does Dietary Quality Play a Role?

Abstract: Information on familial resemblance is important for the design of effective family-based interventions. We aimed to quantify familial correlations and estimate the proportion of variation attributable to genetic and shared environmental effects (i.e., familiality) for dietary intake variables and determine whether they vary by generation, sex, dietary quality, or by the age of the children. The study sample consisted of 1435 families (1007 mothers, 438 fathers, 1035 daughters, and 1080 sons) from the multi-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 57 publications
(68 reference statements)
5
36
0
1
Order By: Relevance
“…In our previous study based on I. Family data, sibling resemblances in food group intake for sister-sister, sister-brother, and brother-brother pairs were about similar in magnitude [3]. Together these results suggest that siblings of the same and opposite sex experience rather similar social environments for eating, but not for screen time, for which siblings of the same sex resembled one another more than opposite-sex siblings.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…In our previous study based on I. Family data, sibling resemblances in food group intake for sister-sister, sister-brother, and brother-brother pairs were about similar in magnitude [3]. Together these results suggest that siblings of the same and opposite sex experience rather similar social environments for eating, but not for screen time, for which siblings of the same sex resembled one another more than opposite-sex siblings.…”
Section: Discussionmentioning
confidence: 58%
“…As children reach preschool and school age, they may modify their behavior as they spend more time away from home and encounter new social influences. Previous IDEFICS/I.Family research showed that younger siblings tended to be more alike in dietary intake than older siblings [3]. Consistent with this observation, twin studies have shown that the shared family environment is the predominant driver of dietary intake in young children [4], whereas this influence disappears by young adulthood [5,6].…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Energy and dietary fiber intake were assessed by repeated 24 hour dietary recalls [33,34]. Usual intakes for fiber were estimated based on the validated National Cancer Institute (NCI) method, which is one of the most widely accepted methods for this purpose [35,36].…”
Section: Methodsmentioning
confidence: 99%
“…Most recent published information indicates dietary phytochemicals play a tremendous role in the prevention of cancer if consumed in adequate quantities and in combination with other lifestyle choices. Mostly positive epidemiological association have been reported between dietary phytochemical consumption and colon cancer, breast cancer, stomach cancer, prostate cancer, ovarian cancer, endometrial and other cancers [1][2][3]. The amount of dietary phytochemicals consumed in most of these studies is typically determined by food recalls, food questionnaires, and food diaries analyzed through different diet analysis software.…”
Section: Editorialmentioning
confidence: 99%